Uji Kinerja Mesin Chopper Serbaguna untuk Memperkecil Ukuran Pucuk Tebu - Fadhil, Naufalda M.; Asmara, Sandi; Oktafri, Oktafri; Suharyatun, Siti (Jurnal Agricultural Biosystem Engineering, 2026)
This study aimed to evaluate the performance of a multipurpose chopper machine in reducing the size of sugarcane tops as a means of utilizing agricultural biomass waste. The research was conducted at the Laboratory of Power and Agricultural Machinery, Faculty of Agriculture, University of Lampung, using a factorial Completely Randomized Design (CRD) with two factors: engine rotation speed (1500, 1700, and 2000 rpm) and feed input (3, 4, and 5 stalks of sugarcane tops). The parameters observed were work capacity, material losses, fuel consumption, and chopping uniformity. The results revealed that both engine speed and feed input had a highly significant effect on all performance parameters. Increasing engine speed enhanced work capacity up to 172.2 kg/hour, reduced material losses to 8.58%, and maintained efficient fuel consumption at 966 ml/hour under the 2000 rpm and 4-stalk combination. The multipurpose chopper machine proved to be effective and efficient in reducing the size of sugarcane tops, making it suitable for use as biomass fuel or alternative livestock feed.